Subjectification by objectification of the African Sub-Saharan children in their relationship with water, localities of Mauritania, Senegal and Togo : subjective development of children 4 to 7 years old envisioned in report to water as a social object - (:unkn) unknown (My University, 2015)
This thesis is inspired by the work on the development of children growing up in disadvantaged living conditions (Zaouche Gaudron, 2005). It treats the subjectification of the African Sub-Saharan children in their relationship with water. In this study, subjectification is the process by which children produce their subjective uniqueness based on the relationship with objective realities in their environment (Malrieu, 2003). Our approach comes back to the classical question in psychology, about the Subject’s activity on the Object. The alternative of the objectification allows us to show that Objects are not only determining factors toward Subjects but, through social mediation, they could become Subjects themselves (Marx, 1867; Vygotsky, 1930; Wallon, 1945; Meyerson, 1948, Sève, 2008). The process of child subjectification does not refer directly to children activity, but to their social objectification, allowing them, through their relationship to objects, to become singulars subjects. Our study sample consists of 68 children, between 4 and 7 years old, who are living in the rural communities of Bogué and Bakel close to the river between Mauritania and Senegal as well as in the rural community of Tomè in Togo close to the river of Egbi. Our research has been based on semi-structured interviews targeting parents or significant adults, and figurative boards targeting children that allow, through water scenes, to be exploited as objectification of three successive phases: “natural” situation, concerted and retentive. Our main results show that when adults are involved in water objectification, through the concerted situation, water becomes a social object intervening in the relationship enabling children more and more to realize their subjectification. The relationship between suitable water and children's development proves that is irreducible to the impact of natural determinations, for example the areas where they live. However, our specific
Keywords: African Research